Assessing the Value of Ecosystem Services From an Indigenous Estate: Warddeken Indigenous Protected Area, Australia - Coyne, Cynthia; Williams, Greg; Sangha, Kamaljit K. (Frontiers in Environmental Science, 2022)
The value of ecological systems to human well-being and the economy is often not estimated in contemporary economic and policy decision making processes. Estimating non-marketable and marketable values of ecosystem services from Indigenous managed land provides significant information about the role that the natural environment plays in maintaining the well-being of people. This research investigates the value of ecosystem services from an Indigenous Protected Area, the Warddeken Indigenous Protected Area—an estate managed by Indigenous people in northern Australia. It provides valuable insights for policy makers, land managers, and future development programs while informing the importance of managing Indigenous lands for the local and wider public benefits. Additionally, applying the Millennium Ecosystem Assessment framework and the standard ecological economic valuation techniques, this study presents ‘realistic’ values of marketable and non-marketable ecosystem services identified from the Warddeken Indigenous Protected Area. The total value of ecosystem services was estimated at $32.6 million per year, which are largely non-marketable (such as climate and water regulation) and these values flow to the local and wider public. This research further argues that investing in managing Indigenous estates helps in reducing welfare costs for the Australian Government worth, in the case of the Warddeken Indigenous Protected Area, $8 million per year. Overall, the value of ecosystem services and cost savings demonstrate the real benefits that Indigenous people obtain for working on their land, termed as “Country.” In addition, Indigenous land management delivers offsite ecological, social, and cultural ecosystem services (value estimated at $29 million per year for the Warddeken Indigenous Protected Area) which are typically ignored in policy decision making regarding Indigenous matters in Australia. This study highlights the importance of land managed by Indigenous people in Australia and worldwide to comprehend the real value of benefits and suggests developing appropriate stewardship arrangements to support people’s efforts.